The English disease in Finnish compound processing: Backward transfer effects in Finnish-English bilinguals - Bertram Raymond; Kuperman Victor (Cambridge University Press, 2022)
Most English compounds are spaced compounds, whereas spelling regulations prescribe Finnish compounds to be written in a concatenated format. However, as in English, Finnish compounds are commonly spaced nowadays (e.g., piha juhla ‘garden party’), a phenomenon that we labeled the ‘English disease’. In this eye movement study with Finnish–English bilinguals we investigate whether the reading of a concatenated or illegally spaced Finnish compound is affected by the spelling of an English translation equivalent (ETE). We found that spaced Finnish compounds were read slower than their concatenated counterparts, but this effect was attenuated when ETEs were thought to be spaced. Similarly, concatenated Finnish compounds were read faster when their ETEs were also concatenated. These backward transfer effects are in line with studies that show that processing behavior in L1 is affected by a strong concurrent L2, even when the L1 is the native language as well as the dominant community language